The youths and their capacity to partner and cooperate in the creation of Wealth in Zimbabwe – a Hunhu/Ubuntu approach - Charamba, Tyanai (Africa Institute for Culture, Peace, Dialogue and Tolerance Studies, 2016)
Like most African countries, Zimbabwe belongs to the category of what Sorensen (2004) has called weak postcolonial states. For Sorensen, most Africa states are weak since they fail to produce enough wealth to sustain their citizens. That being the case, this article argues that, both the development and the future of any country lie with its youths. In fact, the article argues that the youths are the reservoirs of both the energy that is needed for the creation of a country’s wealth. The article further argues that, forthe youths to play their part in the creation of wealth they need to co-operate in good faith: and that they will be incapacitated to play their part if they are alienated from group identity. That is argued to be the case since the youths, who do not have a genuine group identity, will lack an internal spur that will propel them to work together for the benefit of their people. The spur that can propel the youths to partner in the creation of wealth is hunhu/ubuntu. In light of that, the article grapples with what can be considered hunhu/ubuntu in Zimbabwe and also tackles how that which can be considered hunhu/ ubuntu can empower the Zimbabwean youths to co-operate in the process of creating wealth. This article benefits from the use of Freire’s (1972) characteristics of good dialogue and of wa Thiong’o’s (1987) thesis of the “human heart” (1987, P. 51-57).